Role of Hepatitis B Virus Infection in Modulating Immune Biomarkers and Adipokine Levels - Hussein, Afaf Saud (American Journal of Biomedicine and Pharmacy, 2026)
Background & Aim: Immune dysregulation and changes in adipokine levels are one of the characteristics of chronic Hepatitis B virus (HBV) infection. The present study was designed to assess the significance of HBV infection in modulation of immune (IL-6, IL-8, TNF-α and IL-10) and adipokine (adiponectin, leptin and visfatin) biomarkers in Iraqi patients. Materials and Methods: A cross-sectional study was conducted at Azadi Teaching Hospital in Kirkuk, Iraq from April through August 2025; a total of 87 patients with chronic HBV and an equivalent number of healthy controls were included. The immune biomarkers and adipokines concentrations in serum were determined by ELISA, and statistical methods consisting of comparison testing between groups, correlation analysis and ROC curve assessment were adopted. Results: All HBV patients were HBsAg positive (87/87, 100%), while all controls were negative. HBV patients showed significantly higher levels of IL-6 (42.5 ± 12.8 pg/mL), IL-8 (35.6 ± 10.7), TNF-α (28.9 ± 9.3), IL-10 (14.8 ± 5.2), adiponectin (12.6 ± 3.8 µg/mL), and visfatin (18.7 ± 5.6 ng/mL), whereas leptin was slightly lower (9.4 ± 3.1 ng/mL) compared to controls (all p < 0.01). Correlation analysis revealed positive associations between IL-6, IL-8, TNF-α and adiponectin/visfatin, and negative correlations with leptin. ROC analysis indicated that IL-6, IL-8, TNF-α, and visfatin had the highest diagnostic potential (AUC >0.90). Conclusion: Chronic HBV-infected Iraqi patients showed increased immune activity and adipokine imbalance. Immune biomarkers and adipokines, including IL-6, IL-8, TNF-α and visfatin could be used as potential diagnostic and monitoring parameters in HBV.